The cyclicality of immigrant wages and labour market flows: Evidence from Spain - Ismael Gálvez-Iniesta (Economics: The Open-Access, Open-Assessment Journal, 2022)
This article studies the responses of real wages and labour market flows of immigrants in Spain for the period between 1999 and 2019. By using Labour Force Survey microdata, I examine the cyclicality of job-finding and job-separation rates for immigrants and natives over the long Spanish economic expansion and the sharp contraction. During the expansion, 1999-2007, the job-finding rate was higher for immigrants than for natives, but both rates converged to a lower level after the Great Recession took place in 2008. I also find that the impact of the crisis on the job-separation rate was more than three times as high for immigrants than for natives. By using longitudinal social security data, I find that wage cyclicality is higher for immigrants than for natives: a one percentage point increase in the unemployment rate is associated with a 0.61 and 0.85% drop in real wages for natives and immigrants, respectively. However, these differences only occur among low-tenure workers. This study provides novel empirical evidence to enrich macroeconomic theories on the interaction of economic cycles and the impact of immigration.
Keywords: E24; J21; J31; J60; J61; 330; immigration; job-finding rate; job-separation rate; labour market; wage cyclicality